Towards a Critical Reconstruction of Modern Refugee Subjectivity: Overcoming the Threat–Victim Bipolarity with Judith Butler and Giorgio Agamben - Polychroniou Ariadni (De Gruyter, 2021)
The accurate illustration of the contemporary refugee subject has presented an unprecedented theoretical, epistemological and methodological challenge to all fields of academic research. Seeking for alternative philosophical modalities capable of liberating refugee representation from the suffocating threat–victim bipolarity, this article critically investigates Giorgio Agamben and Judith Butler’s theoretical perspectives on refugee subjectivity. Section 1 systematises the dominant tropes of refugee representation either as dehumanised threats or depoliticised victims. Section 2 introduces the readers to Giorgio Agamben’s emblematic homo sacer as a potentially fertile reconceptualisation of refugee subjectivity. In this context, Judith Butler’s critique on the Agambenian bare life is presented in two core pillars. Following one Butlerian claim, we trace the Agambenian inadequacy to successfully overcome the contemporary threat–victim mode of refugee representation in the absence of an empowering theoretical account of the homo sacer’s agentic and resisting capacities. In Section 4, we explore Judith Butler’s main argument regarding the constitutively political character of vulnerable refugee existence. By designating the Butlerian constellation of vulnerability and agency as an invigorating alternative perspective on modern refugee representation, we finally argue that Butler’s epistemological framework provides a more agonistic and nuanced theorisation of refugee subjectivity than Agamben.